Examining the Impact of Economic Policy on the Lives of People with Disabilities in Indonesia (Study in Klantingsari Village) - Pradana, Dicky Putra Surya; Maulana, David; Alfarizki, Rayhan Ahmad; Auliansyah, Arrafi Rahmad; Maulana, Andri (Universitas Muhammadiyah Makassar, 2025)
This study compares the financial health of Bank Muamalat, a national private Islamic bank, and Bank Syariah Indonesia (BSI), a state-owned Islamic bank, based on their 2022 annual financial statements. The analysis applies the RGEC method (Risk Profile, Good Corporate Governance, Earnings, and Capital) to assess their financial performance. Using a quantitative comparative approach, the study evaluates key financial indicators from secondary data sourced from the Financial Services Authority (OJK). The findings reveal that Bank Muamalat demonstrated strong liquidity and capital adequacy but faced challenges in profitability, particularly in return on assets (ROA). In contrast, Bank Syariah Indonesia exhibited superior risk management and operational efficiency, leading to a higher composite score. In 2022, Bank Muamalat received a composite rating of 68.57% (PK-3,